KERJASAMA ANTARA GURU DAN ORANG TUA DALAM PELAYANAN PADA ABK DI TK INKLUSI TUNAS KASIH - Yesi, Fransiska; Syukri, Muhammad; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe study aims to find out the collaboration between teachers and parents in special needs children's services in TK Inclusi Tunas Kasih. The research method used is descriptive in the form of qualitative research. Sources of research data are teachers and parents with interviews and documentation. The results of the study indicate that there is a collaboration program between teachers and parents in providing services for special needs children at TK Tunas Kasih, namely psychological examinations, play therapy, home visits to students, parents invited to school, meetings, letters between school and home, and report cards . The implementation of cooperation programs with parents in providing child services for special needs in kindergarten is carried out in weekly, monthly, quarterly and semester periods. Program evaluation and collaborative follow-up in services to special needs children in kindergarten were conducted at the end of the semester when taking report cards and reports to the foundation. Factors that support collaboration with parents in service to children special needs in kindergarten include internal and external factors. Inhibiting factors for cooperation with parents in child services are special needs in kindergarten, namely lack of budget funds and lack of openness of parents regarding children.Keywords: collaboration between teachers and parents, services for children withÂ  special needs in Inclusion